Implementation of the Return to Work Program as a Guarantee for Protection of Workers' Rights at PT. SPINDO Surabaya - Bagijo, Himawan Estu; Hindiawati , Wahyu (PT. Hafasy Dwi Nawasena, 2024)
Social security in Indonesia is contained in the constitution. The content of this social security is regulated in article 28 H paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states